Sales Fluctuations to Maintain Profits at Alif Frozen Food Stores - Andini Nur Paujiah; Raihani Salsabila; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
Industrial visits to Alif Frozen Food stores were carried out to compare fluctuations in sales before the covid 19 pandemic and during the covid 19 pandemic and what strategies were used by the Alif Frozen Food store to continue to maintain profits with descriptive methods in the form of observations and interviews with store owners. The COVID-19 pandemic has had a significant impact on various business sectors, including Micro, Small and Medium Enterprises (UMKM) such as Alif Frozen Food Stores. Fluctuations in sales of frozen food at the Alif Frozen Food Store experienced a slight increase during the covid pandemic, with the implementation of a sales strategy to continue to maintain profits. The sales strategy to maintain profits in the form of changing the function of the kiosk at the Alif Frozen Food store has helped the store survive during the pandemic, minimize losses and be able to increase sales fluctuations. MSMEs in the frozen food sector such as Alif Frozen Food play an important role in Indonesia's economic development. Therefore, a sales strategy must always be applied to MSMEs to continue to increase sales fluctuations and increase economic growth.